HUBUNGAN PENDIDIKAN, PEKERJAAN DAN SIKAP IBU MENYUSUI TERHADAP PRAKTIK MENYUSUI BAYI USIA 0-6 BULAN DI WILAYAH KERJA UPK PUSKESMAS TELAGA BIRU SIANTAN HULU PONTIANAK UTARA - Trianita, Winda; Nopriantini, Nopriantini (Pontianak Nutrition Journal, 2018)
In the practice of nursing one factor that plays an important role in the success of breastfeeding is feeding techniques. When the breastfeeding technique is incorrect, it can cause a variety of problems. No maximum breastfeeding will result in less good, because the baby’s sucking is very influential on subsequent milk production stimulation. Based on data obtained from UPK Siantan Hulu Health Center Blue Lake District of  North Pontianak, the prevalence of exclusive breastfeeding in 2014 is still low, as much as 61.88% with a target of 80%. This study aims to determine the relationship of education, employment and attitude towards the practice of breastfeeding mothers of infants aged 0-6 months in the working area of   Puskesmas UPK Siantan Upper Blue Lake District of North Pontianak. This type of research is analytic survey with cross sectional approach. Sampling was done by purposive sampling with a sample of 59 people. Data were analyzed by chi square test. The results showed no association between maternal education with the practice of breastfeeding. There is a relationship between the work and the attitude towards the practice of breast-feeding mothers. Suggested to the local health authorities to continue to provide information on the practice of breastfeeding in the right way, through the distribution of posters, leaflets and other education media, and routinely perform counseling and individual and group counseling at health centers or at Posyandu activities.